2022
DOI: 10.1111/mcn.13416
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of gestational weight gain among women with obesity and its correlation with hypertensive disorders of pregnancy in Chinese women

Abstract: Gestational weight management in obese women is critical in clinical work. Adverse pregnancy outcomes are associated with improper gestational weight gain (GWG).However, the pattern of GWG (PGWG) and its correlation with hypertensive disorders of pregnancy (HDP) in obesity are still unclear in China. This retrospective cohort study evaluates clinical data from 799 women through multivariate analyses and trajectory analyses. All the participants are stratified per first trimester weight gain category into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This new Chinese standard of recommendation has been proven more suitable for Chinese people than the US National Academy of Medicine guidelines 23 . In addition, this phenomenon of catch up weight gain in mid‐late pregnancy corroborates with the previous study in our group, which showed that obese women with inadequate weight gain in the first trimester had paradoxically more rapid weekly weigh gain after 20 weeks 24 . According to our optimal weight gain rates, women who had higher weight gain rate increased risk of macrosomia and LGA, which suggested that the early pregnancy weight loss women also need to be aware of excessive weight gain.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This new Chinese standard of recommendation has been proven more suitable for Chinese people than the US National Academy of Medicine guidelines 23 . In addition, this phenomenon of catch up weight gain in mid‐late pregnancy corroborates with the previous study in our group, which showed that obese women with inadequate weight gain in the first trimester had paradoxically more rapid weekly weigh gain after 20 weeks 24 . According to our optimal weight gain rates, women who had higher weight gain rate increased risk of macrosomia and LGA, which suggested that the early pregnancy weight loss women also need to be aware of excessive weight gain.…”
Section: Discussionsupporting
confidence: 89%
“…23 In addition, this phenomenon of catch up weight gain in mid-late pregnancy corroborates with the previous study in our group, which showed that obese women with inadequate weight gain in the first trimester had paradoxically more rapid weekly weigh gain after 20 weeks. 24 According to our optimal weight gain rates, women who had higher weight gain rate increased risk of macrosomia and LGA, which suggested that the early pregnancy weight loss women also need to be aware of excessive weight gain. Due to the low incidences of SGA and full-term LBW in our study, we did not find a relationship between lower weight gain rate and the risk of SGA and full-term LBW.…”
Section: The Relationship Between the Early Pregnancy Weight Loss Gwg...mentioning
confidence: 98%
“…The purpose of this special collection of papers is to bring together research that has been conducted on GWG in China. These papers (Song et al, 2023 ; Wang et al, 2023 ; Yang et al, 2023 ) provide new local evidence that may be used for developing global GWG guidelines.…”
mentioning
confidence: 99%
“…The second paper in this section describes the relationship between GWG timing (each trimester) and hypertensive disorders during pregnancy (i.e. gestational hypertension and pre‐eclampsia) in obese women (Song et al, 2023 ). In their retrospective cohort study, Song et al ( 2023 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation